Human Atrial Arrhythmogenesis and Sinus Bradycardia in KCNQ1-Linked Short QT Syndrome: Insights From Computational Modelling - Whittaker, Dominic G.; Colman, Michael A.; Ni, Haibo; Hancox, Jules C.; Zhang, Henggui (Frontiers in Physiology, 2018)
Atrial fibrillation (AF) and sinus bradycardia have been reported in patients with short QT syndrome variant 2 (SQT2), which is underlain by gain-of-function mutations in KCNQ1 encoding the α subunit of channels carrying slow delayed rectifier potassium current, IKs. However, the mechanism(s) underlying the increased atrial arrhythmogenesis and impaired cardiac pacemaking activity arising from increased IKs remain unclear. Possible pharmacological interventions of AF in the SQT2 condition also remain to be elucidated. Using computational modelling, we assessed the functional impact of SQT2 mutations on human sinoatrial node (SAN) pacemaking, atrial repolarisation and arrhythmogenesis, and efficacy of the anti-arrhythmic drug quinidine. Markov chain formulations of IKs describing two KCNQ1 mutations – V141M and V307L – were developed from voltage-clamp experimental data and then incorporated into contemporary action potential (AP) models of human atrial and SAN cells, the former of which were integrated into idealised and anatomically-detailed tissue models. Both mutations shortened atrial AP duration (APD) through distinct IKs ‘gain-of-function’ mechanisms, whereas SAN pacemaking rate was slowed markedly only by the V141M mutation. Differences in APD restitution steepness influenced re-entry dynamics in tissue – the V141M mutation promoted stationary and stable spiral waves whereas the V307L mutation promoted non-stationary and unstable re-entrant waves. Both mutations shortened tissue excitation wavelength through reduced effective refractory period but not conduction velocity, which served to increase the lifespan of re-entrant excitation in a 3D anatomical human atria model, as well as the dominant frequency (DF), which was higher for the V141M mutation. Quinidine was effective at terminating arrhythmic excitation waves associated with the V307L but not V141M mutation, and reduced the DF in a dose-dependent manner under both mutation conditions. This study provides mechanistic insights into different AF/bradycardia phenotypes in SQT2 and the efficacy of quinidine pharmacotherapy.